2009
DOI: 10.1111/j.1462-2920.2009.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

The turnover of medium‐chain‐length polyhydroxyalkanoates in Pseudomonas putida KT2442 and the fundamental role of PhaZ depolymerase for the metabolic balance

Abstract: Polyhydroxyalkanoates (PHAs) are biodegradable polymers produced by a wide range of bacteria, including Pseudomonads. These polymers are accumulated in the cytoplasm as carbon and energy storage materials when culture conditions are unbalanced and hence, they have been classically considered to act as sinks for carbon and reducing equivalents when nutrients are limited. Bacteria facing carbon excess and nutrient limitation store the extra carbon as PHAs through the PHA polymerase (PhaC). Thereafter, under star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
136
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 54 publications
(90 reference statements)
9
136
0
2
Order By: Relevance
“…It could be suggested that both mutants do not effectively activate processes leading to recovery of energy from PHAs. The number of transcripts of phaC1, phaZ, phaC2 and phaD differed significantly from those of phaF and phaI , which indicates that these operons are differentially regulated, as in de Eugenio et al (2010). According to previous studies (Klinke et al 2000; de Eugenio et al 2010), the phaD gene acts as an activator of the phaC1 and phaI promoters.…”
Section: Discussionmentioning
confidence: 70%
“…It could be suggested that both mutants do not effectively activate processes leading to recovery of energy from PHAs. The number of transcripts of phaC1, phaZ, phaC2 and phaD differed significantly from those of phaF and phaI , which indicates that these operons are differentially regulated, as in de Eugenio et al (2010). According to previous studies (Klinke et al 2000; de Eugenio et al 2010), the phaD gene acts as an activator of the phaC1 and phaI promoters.…”
Section: Discussionmentioning
confidence: 70%
“…Interestingly, more than 150 3-HAs have been identified as constituents of these microbial polymers (most of them summarized by Steinbü-chel and Valentin 1995). Additionally, all HAs are enantiomerically pure and in R-configuration (Ruth et al 2007;De Eugenio et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This cluster encode two class II synthase genes ( phaC1 and phaC2 ) separated by a gene encoding a PHA depolymerase ( phaZ ); a transcriptional activator ( phaD ) and two genes ( phaFI ) encoding phasin-like proteins [2]. In most Pseudomonas, β-oxidation and fatty acid de novo synthesis are used to convert fatty acid or carbohydrate intermediates, respectively into (R)-3-hydroxyacyl-CoAs, which are used as substrates by the Class II PHA synthases [3].…”
Section: Introductionmentioning
confidence: 99%